2014
DOI: 10.1186/1471-2350-15-52
|View full text |Cite
|
Sign up to set email alerts
|

New case of trichorinophalangeal syndrome-like phenotype with a de novo t(2;8)(p16.1;q23.3) translocation which does not disrupt the TRPS1 gene

Abstract: BackgroundTrichorhinophalangeal syndrome (TRPS) is a rare autosomal dominant genetic disorder characterised by distinctive craniofacial and skeletal abnormalities. TRPS is generally associated with mutations in the TRPS1 gene at 8q23.3 or microdeletions of the 8q23.3-q24.11 region. However, three deletions affecting the same chromosome region and a familial translocation t(8;13) co-segregating with TRPS, which do not encompass or disrupt the TRPS1 gene, have been reported. A deregulated expression of TRPS1 has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Li et al (37) identified that the lncRNA ADAMTS9-AS1 served as a novel prognostic biomarker for clinical application in esophageal squamous cell carcinoma. Crippa et al (38) hypothesized that LINC00536 disruption may have contributed to the onset of the clinical trichorhinophalangeal syndrome-like phenotype. Wang et al (39) suggested that WT1 was overexpressed in human hepatocellular carcinoma tissues, and was negatively correlated with overall survival in patients with hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al (37) identified that the lncRNA ADAMTS9-AS1 served as a novel prognostic biomarker for clinical application in esophageal squamous cell carcinoma. Crippa et al (38) hypothesized that LINC00536 disruption may have contributed to the onset of the clinical trichorhinophalangeal syndrome-like phenotype. Wang et al (39) suggested that WT1 was overexpressed in human hepatocellular carcinoma tissues, and was negatively correlated with overall survival in patients with hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Rs116446171 is located near IRF4, DUSP22, and EXOC2, which are implicated in a variety of lymphoid cancers and might represent an important non-coding variant for WM risk (McMaster et al, 2018). Crippa et al (2014) used a probabilistic HMM applied to human embryonic stem cell (HMES) to identify putative regulatory sequences in ChIP-seq data of a patient with trichorhinophalangeal syndrome (TRPS, ORPHA:324764), a complex autosomal dominant malformative disorder, characterized by distinctive craniofacial and skeletal abnormalities.…”
Section: Diagnosis: Mutation Detection And/or Predictionmentioning
confidence: 99%
“… Crippa et al (2014) used a probabilistic HMM applied to human embryonic stem cell (HMES) to identify putative regulatory sequences in ChIP-seq data of a patient with trichorhinophalangeal syndrome (TRPS, ORPHA:324764), a complex autosomal dominant malformative disorder, characterized by distinctive craniofacial and skeletal abnormalities.…”
Section: Epigenetics and Ai In Rds: Existing Literaturementioning
confidence: 99%
“…It was first described in 1966 by Giedion based on three main features of sparse hair, bulbous nasal tip, and short deformed fingers. 1 TRPS Type I is generally associated with mutations or microdeletions in the TRPS1 gene on chromosome 8q23.3, with translocations on this chromosomal arm also reported. 1 The prevalence of TRPS Type I is unknown due to varying and subtle presenting features.…”
Section: Introductionmentioning
confidence: 99%